NARRATIVE STRUCTURE ANALYSIS OF F. SCOTT FITZGERALD’S THE GREAT GATSBY MOVIE - Irawan, Fadhilah; Kristiana, Vera; Nurmala, Dewi (Fakultas Sastra UMN AL Washliyah, 2025)
This thesis analyzes the narrative structure of Baz Luhrmann’s 2013 adaptation of The Great Gatsby using A.J. Greimas’ actantial model. The study aims to explore how the roles of actants influence the story’s progression and themes, and how the narrative structure shapes character relationships within the film. Employing a qualitative descriptive method, the research identifies and categorizes the six actants—Subject, Object, Sender, Receiver, Helper, and Opponent—within the movie’s plot. The analysis reveals that Jay Gatsby functions as the Subject in pursuit of Daisy Buchanan, the Object, with the supporting characters embodying various actantial roles that shape the film’s development. The study also applies Greimas’ canonical narrative schema to examine the narrative progression through stages of Manipulation, Competence, Performance, and Sanction. Findings show that the movie’s narrative structure not only follows a classical storytelling model but also reflects deeper socio-cultural themes such as the illusion of the American Dream, class struggle, and identity. Through this approach, the research highlights how structuralist narrative theory enhances the understanding of character dynamics and thematic complexity in cinematic adaptations of literary works.